Understanding registered nurse decision‐making, communication and care delivery between emergency departments and residential aged care facilities: A research protocol. (28th November 2019) - Gurung, Apil; Broadbent, Marc; Bakon, Shannon; Hocking, Julia; Glenwright, Amanda; Shaw, Christine; Tweddell, Sheryl; Clark, Sean
Abstract: Objectives: Nursing staff in residential aged care facilities (RACF)s often make decisions about the transfer of residents to the emergency department (ED). This paper describes the protocol of a study that aims to understand decision‐making process utilised by RACF registered nurses (RNs) and to explore the perceptions of RNs about the decision and communication process between RACF and ED. Methods: The proposed mixed‐method study will survey and interview RACF RNs to understand their decision to transfer a resident and collect information about older people referred to the ED. Data collection will involve telephone survey, ED information system (EDIS) data and semistructured interviews. Results: The project outcomes will provide an understanding of existing ED service provision, communication between facilities and the reasons for transfer of older person to ED. This may inform redesign in communication processes between the ED and local RACFs and outreach care from the ED to RACFs.